Multi‐Color 3D Printing via Single‐Vat Grayscale Digital Light Processing. (15th April 2022) - Peng, Xirui; Yue, Liang; Liang, Sizhuang; Montgomery, Stuart; Lu, Chunliang; Cheng, Chieh‐Min; Beyah, Raheem; Zhao, Ruike Renee; Qi, H. Jerry
Abstract: Digital light processing (DLP) is a high‐resolution, high‐speed additive manufacturing method that builds 3D parts by selectively curing photopolymerizable resins layer‐by‐layer. To achieve multi‐color DLP printing, researchers have used multiple switchable resin vats. However, these methods require complex vat switching devices and cleaning manipulations, leading to low efficiency. Therefore, it remains a challenge to achieve multi‐color DLP 3D printing efficiently. In this study, a single‐vat multi‐color DLP 3D printing by using an anthraquinone‐based dye is realized. The dye can be oxidized by the free radicals released from photoinitiators under ultraviolet light and change the color from blue to yellow. This color‐changing mechanism permits a graded spectrum of colors as concomitants of the photopolymerization process during DLP printing by controlling the light dose without using extra vats or devices. Multi‐color demonstrations, such as engineering stress simulation results in 3D and multi‐color vases, are successfully fabricated, showing great versatility and efficiency. Abstract : A single‐vat multi‐color digital light processing (DLP) 3D printing is developed using an anthraquinone‐based dye with photocurable inks. The dye can be oxidized by the free radicals released from photoinitiators under UV light and change the color. This color‐changing mechanism permits a graded spectrum of colors as concomitants of the photopolymerization process during DLP 3D printing.